Influence of corrugation size and location on sensitivity enhancement for MEMS-based pressure sensor / Seyed Farhan Moosavian ... [et al.] - Moosavian, Seyed Farhan; Borzuei, Daryoosh; Farajollahi, Meisam; Goharzay, Mehrad (Universiti Teknologi MARA, 2022)
In this paper, a MEMS capacitive diaphragm-based pressure sensor is investigated. The main focus of this work is to analyze the effect of the geometry and configuration on the sensitivity of a sensor as a crucial parameter in sensor design. Finite element modelling using ABAQUS software is conducted to simulate the behaviour of the diaphragm with different geometries under the same condition. Three popular geometries including square, rectangular and circular shapes with similar areas are investigated and sensitivities of 0.3, 0.24, and 0.22 μm/MPa were obtained for circular, square, and rectangular shapes respectively. Corrugated structure is added to circular diaphragm and deflection and stress analysis are provided for various positions and wave radius of the corrugated region and the best configuration based on sensitivity analysis is proposed. Simulation proved the 17.62% improvement in sensitivity by using a corrugated structure in a circular diaphragm with a small wave radius at the circumference of the circle. An increasing number of corrugated wave regions was also simulated but could not enhance the sensitivity in comparison with a one-wave corrugated structure.